Antibacterial effect of ethanol extract of nutmeg against foodborne disease pathogens - Eka Astuty; Eka Sukmawaty (STKIP Persada Khatulistiwa Sintang, 2022)
Foodborne disease is a disease that occurs as a result of food contamination by microbes or harmful chemicals. Nutmeg (Myristica fragrans Houtt.) is widely used as a spice and flavor enhancer for food and beverages. In addition, it has traditionally been used to treat diarrhea and kidney disease. Several pharmacological studies have reported the antioxidant, antimicrobial, antidiarrheal and anti-inflammatory activity of this plant. Antibacterial effectiveness test of nutmeg against several pathogens in this study was carried out using the disc diffusion method. The results of this study indicated that the ethanol extract of flesh of fruit (concentration of 5%, 10%, 15%, 20%, and 25%) had antibacterial activity against all tested pathogenic bacteria. Different results were shown by the ethanol extract of seed and mace. All the ethanol extract concentrations of seed were not able to inhibit the growth of Shigella sp. and Clostridium sp., while the ethanol extract of mace in all concentrations was unable to inhibit the growth of Shigella sp. Various factors may affecting this extract and compound activity when used in complex biological systems such as in vivo and human studies. Future studies must also focus on aspects of pharmacokinetics and toxicological plant extracts and phytochemicals.